The potential of breast cancer screening in Europe - Zielonke, Nadine; Kregting, Lindy M.; Heijnsdijk, Eveline A. M.; Veerus, Piret; Heinävaara, Sirpa; McKee, Martin; Kok, Inge M. C. M.; Koning, Harry J.; Ravesteyn, Nicolien T. (International journal of cancer, 2021)
Currently, all European countries offer some form of breast cancer screening. Nevertheless, disparities exist in the status of implementation, attendance and the extent of opportunistic screening. As a result, breast cancer screening has not yet reached its full potential. We examined how many breast cancer deaths could be prevented if all European countries would biennially screen all women aged 50 to 69 for breast cancer. We calculated the number of breast cancer deaths already prevented due to screening as well as the number of breast cancer deaths which could be additionally prevented if the total examination coverage (organised plus opportunistic) would reach 100%. The calculations are based on total examination coverage in women aged 50 to 69, the annual number of breast cancer deaths for women aged 50 to 74 and the maximal possible mortality reduction from breast cancer, assuming similar effectiveness of organised and opportunistic screening. The total examination coverage ranged from 49% (East), 62% (West), 64% (North) to 69% (South). Yearly 21 680 breast cancer deaths have already been prevented due to mammography screening. If all countries would reach 100% examination coverage, 12 434 additional breast cancer deaths could be prevented annually, with the biggest potential in Eastern Europe. With maximum coverage, 23% of their breast cancer deaths could be additionally prevented, while in Western Europe it could be 21%, in Southern Europe 15% and in Northern Europe 9%. Our study illustrates that by further optimising screening coverage, the number of breast cancer deaths in Europe can be lowered substantially. What's new? Breast cancer is the leading cause of death among European women. Although screening for breast cancer is available in all European countries, not all eligible women aged 50‐69 get screened. Here, the authors calculated how many deaths could be prevented if screening coverage reached 100%, considering both organized and opportunistic screening. Already, screening prevents 21 680 deaths per year, and if all countries reached full examination coverage, an additional 12 434 deaths per year could be prevented across Europe.